2010
DOI: 10.1021/nn100262h
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Uptake of Gold Nanorods by Primary Human Blood Phagocytes and Immunomodulatory Effects of Surface Chemistry

Abstract: Nanoparticle-based in vivo applications should consider the omnipresence of the phagocytes in the bloodstream and tissue. We have studied the nanoparticle uptake capacities of the most important human primary leukocyte populations using a nanoparticle library encompassing both rod-shaped and spherical gold nanoparticles with diameters between 15 and 50 nm and a variety of surface chemistries. Cetyltrimethylammoniumbromide (CTAB)-stabilized nanoparticles were internalized rapidly within 15 min and in large amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
239
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 224 publications
(248 citation statements)
references
References 53 publications
9
239
0
Order By: Relevance
“…Many nanomaterials have been reported to induce inflammatory responses, such as silica nanoparticles, cetyltrimethylammonium bromide-coated gold nanorod, and titanium dioxide nanoparticles (43)(44)(45). However, few studies have focused on the effect of nanoparticles on TLR stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Many nanomaterials have been reported to induce inflammatory responses, such as silica nanoparticles, cetyltrimethylammonium bromide-coated gold nanorod, and titanium dioxide nanoparticles (43)(44)(45). However, few studies have focused on the effect of nanoparticles on TLR stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The endocytosis of NMs by macrophages has been well documented in the literature, [5][6][7][8][9] and it has been reported that NMs with high surface charge and large particle size are phagocytized more efficiently by macrophages. 6,7 The shape of NMs has a profound impact on their endocytosis by macrophages as spherical particles have 5,9 Besides the physicochemical properties of NMs, the macrophage phenotype also has a great impact on NM endocytosis.…”
Section: Introductionmentioning
confidence: 97%
“…Many studies have undertaken investigations into how differently shaped NPs may interact with, or be internalised by mammalian cells [19], yet in order to fully comprehend the potential of alternatively shaped GNPs for biomedical applications, their biochemical impact must also be considered [20]. However, understanding as to how the manipulation of GNP shape relates to their biocompatibility is equivocal [5,21,22].…”
Section: Introductionmentioning
confidence: 99%